Electrocution-related fatalities in Eastern Province of Saudi Arabia: a 24-year retrospective autopsy study - Marwa Al Bayat; Omar Baadheem; Abdul Rahman Al Zahrani; Majdi Al Rabiea; Abdul Salam Al Ruwaili; Fatimah Al Bahraini; Sahar Y. Issa (Egyptian Journal of Forensic Sciences)
Abstract Background Fatal injuries caused by electrocution have been documented worldwide, but detailed studies focusing on their patterns and demographic distribution in Saudi Arabia are limited. This study investigates the characteristics and forensic findings of electrocution-related deaths in the Eastern Region, Saudi Arabia, over two decades. The study analyzed 73 cases of electrocution-related deaths reported to the Forensic Medicine Department in the Eastern Region, Saudi Arabia, from 2000 to 2023. Data on demographic, occupational, autopsy, and histopathological findings were collected and evaluated. Results Most victims were non-Saudi nationals (78.1%), with males constituting 95.8% of the cases. The age groups most affected were 31–40 years (34.25%) and 21–30 years (30.14%) (p = 0.001). The majority of deaths were accidental (98.6%), with only one recorded case of suicide. Histopathological findings revealed inflammatory cell infiltration (20.5%) as the most frequent observation, followed by subcutaneous hemorrhage (13.7%) and cardiac myocyte damage (11%). Toxicological findings were negative in most of the cases (82%). Conclusions The study identifies young non-Saudi male workers as high-risk, underscoring the critical need for enhanced occupational safety protocols. Graphical Abstract